(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Training methods are commonly studied using lineal and quantitative research, limiting the possibilities to proof new ways of optimizing the training process. The aim of the study was to compare the classical strength training appro- ach, based on repetitions, with differential training for the improvement of difﬁ culty elements in aerobic gymnastics applying a linear and a nonlinear tool for analyzing the interaction between load and performance. Two female national standard aerobic gymnasts followed three periods of training (TTa: 5 weeks of traditional training; DT: 8 weeks of differential training; TTb: 5 weeks of traditional training). Load applied to the gymnasts was expressed quantitatively (quantitative load) with an equation including time of execution (t), number of series (N), number of exercises in each series (Rp) and relative intensity, and qualitatively (qualitative load) deﬁ ning the number of different exercises performed. Performance was deﬁ ned through 6 tests based on the execution of three different push-ups. Quantitative and qualitative load, the time of execution of the push ups and the time of ﬂ ight of the jumps were determined weekly during the 17 weeks. The interaction between the load applied to upper limbs and performance of push ups, and the interaction between the load applied to lower limbs and performance of jumps were analyzed using a non-linear metamodel (PerPot) and cross correlations. Push ups results show that the increase in load quantiﬁ ed qualitatively correlates more positively with the increase in performance than with the increase in load measured quantitatively. This suggests that subjects respond better to an increase in the variation of training stimulus than to an increase in the number of repetitions. Nevertheless, PerPot proposes a reduction in the number of varied exercises in the DT period. Regarding jumping tests, the performance of both subjects remained constant, suggesting that four months of training was not enough to improve the time of ﬂ ight in experienced gymnasts, or the training methods were not the most adequate. This study suggests that (1) differential training seems to lead to a greater increase in performance than traditional training, but (2) the same results could be achieved by reducing the number of varied exercises or combining both approaches. Keywords: non-linear metamodel, qualitative load, performance.